2004
DOI: 10.1002/pi.1383
|View full text |Cite
|
Sign up to set email alerts
|

Cationic electron‐beam curing of a high‐functionality epoxy: effect of post‐curing on glass transition and conversion

Abstract: This paper reports on the cationic electron‐beam curing of a high‐functionality SU8 epoxy resin, which is extensively used as a UV‐curing negative photoresist for micro‐electronics machine systems (MEMS) applications. Results show that elevated post‐curing treatment significantly increased both the conversion and the glass transition. The degree of conversion and the glass transition temperature were measured by using Fourier‐transform infrared (FTIR) spectroscopy and modulated differential scanning calorimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…Feng and Farris [28] found that the Tg is approximately identical to the baking temperature when the processing temperature is less than 220°C and increasing in deviation at higher temperature ranges to a maximum Tg of 238°C at a baking temperature of 300°C, which corroborates with the finding of LaBianca [29]. The Tg of post cured SU8 films has been reported to be always higher than the PEB curing temperature of about 40-70°C [30].…”
Section: Glass Transition Temperaturesupporting
confidence: 79%
See 2 more Smart Citations
“…Feng and Farris [28] found that the Tg is approximately identical to the baking temperature when the processing temperature is less than 220°C and increasing in deviation at higher temperature ranges to a maximum Tg of 238°C at a baking temperature of 300°C, which corroborates with the finding of LaBianca [29]. The Tg of post cured SU8 films has been reported to be always higher than the PEB curing temperature of about 40-70°C [30].…”
Section: Glass Transition Temperaturesupporting
confidence: 79%
“…It can be observed that the Tg is always higher than the PEB temperatures by about 80°C for the HP and HY processed samples and approximately 100°C for the VFM samples. Similar findings have been made by Rath et al [30] who reported Tg of about 40-70°C above the PEB temperature. The Tg values predicted by the Di Benedetto equation seem to be reasonable, although maybe higher than those found in literature.…”
Section: Glass Transition Temperaturesupporting
confidence: 79%
See 1 more Smart Citation
“…This approach is superior to radical polymerization, in which the fast diffusion of radicals and the accompanied refractive index change during polymerization result in less control over microstructure formation. 32,33 Poly(HEMA) is a widely used hydrogel that swells in aqueous solution and has been used in many biomedical applications, such as tissue implant, drug delivery, and contact-lens applications. 34 In this negativetone resist system, the structure can be written by lightinduced cross-linking of the hydroxyl groups of poly(HEMA) via a cross-linker (TMMGU, tetramethoxymethyl glycoluril) which in turn is activated by a photoacid generator.…”
mentioning
confidence: 99%
“…The use of radiation curing has been shown to give faster cure rates. This includes the use of microwave curing [19][20][21], UV [22][23] and ebeam [24][25][26] for curing of thin film thermosetting polymers have been shown to give practical and effective advantages [19][20][21]. N-acryloylmorpholine shows a capability to dissolve traditional BMI with high concentration.…”
Section: Introductionmentioning
confidence: 99%